IPTEKS TEKNOLOGI INFORMASI TERHADAP AUDIT INTERNAL PADA PT. BANK SULUTGO - Sitaneley, Jennifer N.; Sabijono, Harijanto (Universitas Sam Ratulangi, 2018)
Following the development of an increasingly advanced era. Information technology comes with a positive impact on internal audits. The correct use of information will affect the audit process. With the help of additional technology, it will facilitate the company in the audit process. Information Technology (IT) for SulutGo Bank increasingly plays a key role in achieving company goals in the business field as well as a means to improve compliance aspects and the implementation of good corporate governance. This study itself aims to see the impact of the use of information technology used during the internal audit process of PT. SulutGo Bank. Based on applicable standards. On the other hand, of course information technology can also create new risks, but this can be overcome by using special controls on information technology systems. The impact of Information Technology itself has an impact on internal auditors to improve Information Technology knowledge and skills and adjust how they are do their work.Keywords : Internal Audit, Information Technology (IT)